A Conceptual Framework: God's Grand Design to Meet the Grand Challenge of Smart Decarceration. - Bermejo, Emilio R.; Hughes, John (Social Work & Christianity)
The U.S. is presently the world leader in incarceration, placing more people in prison than any other nation. This nation's overreliance on a retributive approach to crime and punishment, especially drug-related offenses, has targeted communities of color and failed to achieve reduced rates of crime and drug use. This article presents a conceptual framework that integrates theology and social work practice for Christian practitioners and leaders to "work for the peace and prosperity (shalom) of the city" (Jeremiah 29:7). Shaped by the biblical grand narrative in which God is restoring all of creation to its original design of shalom, this conceptual article also explores biblical justice and how its restorative nature gave birth to the restorative justice movement. When shaped by the biblical grand narrative, social work values, knowledge, and skills give direction and purpose for Christian social workers and faith communities to engage in the Grand Challenge to promote smart decarceration.